Avaliação de desempenho de tecidos quanto a proteção solar e conforto térmico - Santos, Arielma Marques dos (2019)
Sunlight is composed by a series of radiations, which, although essential for life, can negatively impact individual’s health over prolonged and reiterative exposure. Ultraviolet (UV) radiation is one of the main contributing factors for development of skin-related diseases, including cancer, and clothes are considered the main method of protection. This research characterizes fabrics in clothes worn by workers that carry out outdoor activities, exposed to solar radiation, with the aim of indicating variables that affect Ultraviolet Protection Factor (UPF) and thermal comfort of materials and the actual protection they provide, as a way to contribute to a better quality of life and health of these individuals. Different types of fibers in different colors were analyzed. Sample surfaces were characterized by means of optical microscopy and 3D optical profiling. UV (290-400 nm) absorbance, transmittance and reflectance, and infrared absorption (700-1400 nm) were obtained with UV/Vis spectrophotometry. Tests and calculus for UPF determination were based on the AS/ZN 4399:1996 – Sun protective clothing – Evaluation and classification technical regulation. Results showed that fabric composition, color and photodegradation caused by wear under exposure were key factors to ensure solar protection and thermal comfort; other variables such as hairiness and home care showed some influence only over UPF.